Teaching practical science online using GIS: a cautionary tale of coping strategies. Issue 3 (3rd July 2017) - Argles, Tom
Abstract: Strong demand for GIS and burgeoning cohorts have encouraged the delivery of GIS teaching via online distance education models. This contribution reviews a brief foray (2012–2014) into this field by the Open University, deploying open source GIS software to enable students to perform practical science investigations online. The "Remote observation" topic spanned four science disciplines in 6 weeks – an ambitious remit within an innovative overarching module. Documenting the challenges and strategies involved, this paper uses forum usage and student feedback data to derive insights into the student experience and the pitfalls and pleasures of teaching GIS at a distance.